2006
DOI: 10.1038/oby.2006.249
|View full text |Cite
|
Sign up to set email alerts
|

The Figure Rating Scale as an Index of Weight Status of Women on Videotape

Abstract: Research Methods and Procedures: Seventy-two women drawn from a community sample participated in a videotaped study in which height and weight were measured. The FRS is a rating scale displaying 9 silhouettes ranging from very thin to very obese. Women were assigned a figure rating "in-person" by a research assistant (FRS used as a 17-point scale) and by additional research assistants viewing women only on videotape (FRS used as both a 17-and 9-point scale). Pearson's correlation coefficients were calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 8 publications
(10 reference statements)
1
37
0
Order By: Relevance
“…The interaction of maternal weight status with many negative life events was suggestive (P = .12). Among children of mothers with a figure rating $5 (a value sensitive and specific for obesity in previous work 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of maternal weight status with many negative life events was suggestive (P = .12). Among children of mothers with a figure rating $5 (a value sensitive and specific for obesity in previous work 19 …”
Section: Resultsmentioning
confidence: 99%
“…The data set includes only maternal BMI by selfreport when the child is age 15 years. Mothers' images on videotape at child ages 15, 24, and 36 months were assigned a weight status ranging from 1 (thinnest) to 9 (heaviest) by using a standard pictorial rating scale, 18 an approach with demonstrated validity, 19 and ratings were then averaged. The mean maternal weight status rating correlated with maternal BMI when the child was aged 15 years (r = 0.74).…”
Section: Covariatesmentioning
confidence: 99%
“…Figure ratings based on pictorial scales correlate with actual measured weight status (35)(36)(37), with r = 0.87 using the 9-point Stunkard Figure Rating Scale (35) with videotape images and BMI (38). Mothers' images on videotape when the child was 15 mo (n = 1114), 24 mo (n = 1161), and 36 mo (n = 1175) were therefore assigned a figure rating from the Stunkard Figure Rating Scale from 1 to 9; higher ratings represent a higher BMI.…”
Section: Covariatesmentioning
confidence: 99%
“…Respondents were asked to indicate which figure they believed looked like their bodies the most. Some studies have shown that the scale has been a valid and reliable measure of body image (24,25). In this study, convergent construct validity based on the relationship between body image and BMI was 0.707 (P < 0.01).…”
Section: Methodsmentioning
confidence: 49%